(untitled) (Cuestiones de Género: de la igualdad y la diferencia, 2021)
Despite educational advances in Brazil, female representation in science, technology and engineering (STE) is still something to be achieved. Women and men still tend to focus on different areas, on occupational segregation. The aim of the article is to analyze female underrepresentation in the courses at the Technological Center of a public university in Brazil. It was found that the sexual division of labor and education can reinforce certain gender stereotypes. The analyzed data indicate that more men than women take courses in the areas of exact sciences and engineering and that, among women, brown and black women are represented in fewer numbers. Therefore, there is a gender gap in female participation in STE at the investigated university.